Pemberian Minuman Fungsional Campuran Kedelai dan Pisang Menurunkan Kadar Glukosa Darah Pasien Diabetes Melitus - Suhaema Suhaema; Fifi Lutfiah; Ni Ketut Sri Sulendri; Tutut Zikria Anjani (Poltekkes Kemenkes Mataram, 2019)
Indonesia is currently the fourth country with the largest number of DM patients in the world. Functional food is beneficial for the health of DM patients, for example bananas and soybeans. Kepok bananas contain dietary fiber inulin and antioxidants (β carotene). Soybeans contain isoflavones, fiber, and proteins in the form of amino acids arginine and glycine. This study aims to look at the effect of giving functional drinks a mixture of soybean and banana milk on decreasing fasting blood glucose levels in type II DM patients. Type of Quasy-experimental research with pre test and post test with control group design. Subjects were taken using the Simple Random Sampling method and the subjects involved until the end of the study were 26 people. The intervention was carried out for 14 days and given as much as 330 ml. The equality of the subject characteristics of the two groups was analyzed using the chy squere test, and the effect of giving intervention materials on decreasing blood glucose levels was tested by independent t test. The results of the study were characteristics (84.6%) aged 50-60 years, (53.8%) female gender, (57.1%) having a family history of disease, 58.4% using glibenclamide anti-hyperglycemic drugs and BMI average in the risk category. . Result Δ It is known that there is an effect of giving functional drinks on decreasing fasting blood glucose levels where the average change is 11.5 mg / dl (p = 0.03).